187: Changing Pain Management Practices in a Pediatric ED: Teamwork Works!. Issue 6 (1st June 2014) - Trottier, ED; Ferlatte, N; Gaucher, N; Canuel, A; Martineau, M; Hogue, C; Sanchez, M; Certain, M; Lemay, S; Gravel, J
Abstract: BACKGROUND: Pain control in pediatric emergency department (PEDs) is often suboptimal, but quality improvement (QI) initiatives to change healthcare providers' practices are often fraught with difficulties. OBJECTIVES: To develop a multidisciplinary team approach to the management of pain in a PED, in order to improve procedural pain control. DESIGN/METHODS: In spring 2013, an interdisciplinary group of ED staff (nurses, physicians, administrative) from a tertiary care pediatric university hospital was created to explore pharmacological and non-pharmacological opportunities to improve pain relief in ED patients. Frequent, brief meetings – in collaboration with hospital pharmacists, pain management researchers, and the hospital's pain team - allowed for the identification of barriers to pain management, areas needing improvement and easy, low-cost solutions that would be acceptable with minimal staff resistance. To assist these practice changes, one nursing team was identified as test group, facilitating feedback about chosen methods and enhancing both the pain team's and the staff's capacity to adapt to barriers to implementation. During the trial period, structured written feedback (quantitative and qualitative) was provided for every intervention to guide choices. Training regarding new approaches was then provided to all PED physicians and nurses. Venipuncture was chosen as the first QI initiative. RESULTS: The table presents achieved practice changes to reduce procedural pain during venipuncture (six months after pain team's creation). The topical anesthetic was chosen based on literature review but also on written comments from nursing staff regarding pain control efficacy, loss of vascular anatomy and ease of use. CONCLUSIONS: Using an interdisciplinary approach to pain management methods allowed for the development of creative, realistic, low-cost and achievable goals in a short time span. Also, implementing the project progressively allowed for constant, immediate feedback and adjustments. Such working models could be used to create various clinical guidelines and to facilitate actual practice changes.